Bradycardiac Angina: Haemodynamic Aspects and Treatment. Issue 5636 (11th January 1969) - Fowler, P. B. S.; Ikram, H.; Maini, R. N.; Makey, A. R.; Kirkham, J. S.
Abstract : A patient with a sinus bradycardia and angina is described who was unable to increase his heart rate on vigorous exercise by more than a few beats. His severe angina was attributed to the bradycardia. Atrial pacing of his heart abolished his angina and increased his exercise tolerance. Circulatory changes at rest, on exertion, and with atrial pacing are described. The cause of angina in this patient is discussed.